How to turn POTEntial Alumni into Alumni with POTEntial - Somodi, Klára; Abada, Alan (ICAReAlumni Conference Proceedings, 2022)
The aim of this paper is to present the collaborative approach the Alumni Team of the University of Pécs Medical School (UPMS) initiated, piloted, and carried out in two consecutive semesters. This approach, the Junior Alumni Program (JAP), aims to equip students with the soft skills and career guidance needed to excel during their educational journey and beyond. The program offers workshops and resources which were intentionally designed to complement the traditional curriculum. By harnessing the experience and expertise of successful alumni, students gain exclusive access to knowledge and opportunities through the extensive POTE (POTE is the Hungarian abbreviation of the Medical University of Pécs) network. As a bonus, ‘regular’ Alumni involvement is growing exponentially through Junior Alumni events. The Alumni Team is dedicated to turn POTEntial Alumni into Alumni with POTEntial.